Optimization of flood inundation simulation using multi-resolution Digital elevation model - Abdul Kadir, Muhammad Azraie (2022)
Several studies have been made to improve the flood inundation simulation derived from coarser Digital Elevation Model (DEM) such as using modification spatial distribution of DEM and modification of the river cross section. All models focused on the DEM. Up until now, optimization studies of DEM resolution with flood inundation distribution relationship is scarce. This is one of the key components of flood phenomenon which requires high accuracy for further action in the flood risk management. Additionally, inflow value could also be used to optimize flood inundation simulation without disturbing the coarse DEM. In this study, the relationship between DEM resolution and flood inundation prediction was determined in an attempt to propose a new optimization method of flood inundation prediction. This was established by incorporating the inflow value into the relationship between DEM resolution and flood inundation. A hydraulic model of Sungai Bertam, Cameron Highland was developed at a scale of 1:25 to conduct experiments at different inflow value. This result was used to validate the 2D numerical simulation of HEC-RAS model. Then, the high resolution DEM was resampled into several coarser DEM to re-simulate the flood inundation. Both DEM and flood inundation results (Water Surface Elevation (WSE), flood extent, and flood area) were used to determine the effect of inflow parameter on the optimization of flood inundation simulation. Additionally, the optimization was also validated experimentally using the hydraulic model. Hydraulic model experiment indicated that the geometry of the channel (shape and slope) plays an important role in flood inundation and inflow of 64 l/s provided a significant flood inundation at the downstream of the river. A good agreement between hydraulic and HEC-RAS model was found except at low inflow (25 m3/s and 50 m3/s), velocity (maximum Mean Relative Absolute Error (MRAE) = 0.408) and flow travel time (R2 = 0.595). This is due to the limitation of diffusive wave algorithm, 2-dimensional model and effect of grid configuration. Relationship between DEM resolution and WSE gave the best R2 with minimum R2 = 0.9845 at the inflow of 150 m3/s. Increasing DEM resolution also increased the Mean Absolute Error (MAE) and MRAE index. Optimization using the relationship between DEM resolution and WSE together with several inflow values gives significant improvement up to 72 % of MRAE index for flood extent and 131.53 % of MRAE index for flood area. Validation using the hydraulic model experiment at an inflow of 200 m3/s indicated that the optimization improves the MRAE index of WSE by 23%. The study concluded that flood inundation simulation can be improved by modification of the inflow parameter, as well as the correlation between DEM resolution and flood inundation prediction.